Obesity, Sex, Snoring and Severity of OSA in a First Nation Community in Saskatchewan, Canada - James A. Dosman; Chandima P. Karunanayake; Mark Fenton; Vivian R. Ramsden; Jeremy Seeseequasis; Robert Skomro; Shelley Kirychuk; Donna C. Rennie; Kathleen McMullin; Brooke P. Russell; Niels Koehncke; Sylvia Abonyi; et al. (Clocks & Sleep, 2022)
Sleep disorders have been related to body weight, social conditions, and a number of comorbidities. These include high blood pressure and type 2 diabetes, both of which are prevalent in the First Nations communities. We explored relationships between obstructive sleep apnea (OSA) and risk factors including social, environmental, and individual circumstances. An interviewer-administered survey was conducted with adult participants in 2018–2019 in a First Nations community in Saskatchewan, Canada. The survey collected information on demographic variables, individual and contextual determinants of sleep health, and objective clinical measurements. The presence of OSA was defined as an apnea–hypopnea index (AHI) ≥5. Multiple ordinal logistic regression analysis was conducted to examine relationships between the severity of OSA and potential risk factors. In addition to the survey, 233 men and women participated in a Level 3 one-night home sleep test. Of those, 105 (45.1%) participants were reported to have obstructive sleep apnea (AHI ≥ 5). Mild and moderately severe OSA (AHI ≥ 5 to <30) was present in 39.9% and severe OSA (AHI ≥ 30) was identified in 5.2% of participants. Being male, being obese, and snoring loudly were significantly associated with severity of OSA. The severity of OSA in one First Nation appears relatively common and may be related to mainly individual factors such as loud snoring, obesity, and sex.